Karate basics - Rielly, Robin L.
Karate Basics teaches you all the fundamentals of this ancient martial art form in a clear and easy-to-understand manner! This book contains the following vital information: the origins of karate-its philosophy, history, and different schools; how to find a teacher and a class that are right for you; getting ready for your first class-what actually happens in a karate class?;The essential elements-stances, blocks, thrusts, trikes, punches and kicks; how to complement your karate training with sparring drills and kata; effective ways to succeed in karate-how to create a training program, test for belt promotion, and an overview of competitions and tournaments; resources to help you develop your knowledge and understanding of karate. Whether you're just getting started, or have already been training for a year of two, Karate Basics offers an easy, yet comprehensive introduction to the sport that will make you feel more confident and enable you to become successful much more quickly